REGIONAL INTEGRATION: ORGANIZATIONAL COOPERATION THROUGH A CULTURAL APPROACH (CASE STUDY IN YOGYAKARTA) - Anwar, Anwar (Kementerian Pendidikan dan Kebudayaan, 2020)
This research focuses on Human Rights in Yogyakarta. Seeing ASEAN in cooperation in promoting and protecting Human Rights with Non Government Organizations (NGOs) at the regional level. This research is a research in the discipline of international relations, but this research uses qualitative methods with data collection techniques, namely observation and interviews. The results of the study indicate that this form of cooperation does not occur formally but occurs informally. Each organization has a special mechanism for promoting and protecting human rights. These findings constitute a long process of interpretive analysis so as to answer research questions and discover new findings. Cultural factors influence the process of socialization and cooperation in upholding each person's human rights.Â